2020
DOI: 10.3233/adr-200214
|View full text |Cite
|
Sign up to set email alerts
|

Race- and Sex-Based Disparities in Alzheimer’s Disease Clinical Trial Enrollment in the United States and Canada: An Indigenous Perspective

Abstract: Randomized clinical trials (RCT) involve labor-intensive, highly regulated, and controlled processes intended to transform scientific concepts into clinical outcomes. To be effective and targeted, it is imperative they include those populations who would most benefit from those outcomes. Alzheimer's disease (AD) is most detrimental to the aging population, and its clinical manifestation is influenced by socioeconomic factors such as poverty, poor education, stress, and chronic comorbidities. Indigenous populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Their trial participation has been suppressed by mistrust of clinical research based on historical mistreatment, language and cultural barriers, and limited access to health care, among other barriers 7,9,26 . Moreover, inadequate targeted recruitment of diverse groups has exacerbated the underrepresentation of high‐risk populations and limited our understanding of whether biomarker and pathological changes are similar across groups 9,23,25,27–29 . These groups are also less likely to receive a timely AD diagnosis, and therefore when they are diagnosed, the diagnosis typically comes in the later stages of the disease when their symptoms are more debilitating 30 .…”
Section: Barriers To Clinical Trials For Admentioning
confidence: 99%
See 1 more Smart Citation
“…Their trial participation has been suppressed by mistrust of clinical research based on historical mistreatment, language and cultural barriers, and limited access to health care, among other barriers 7,9,26 . Moreover, inadequate targeted recruitment of diverse groups has exacerbated the underrepresentation of high‐risk populations and limited our understanding of whether biomarker and pathological changes are similar across groups 9,23,25,27–29 . These groups are also less likely to receive a timely AD diagnosis, and therefore when they are diagnosed, the diagnosis typically comes in the later stages of the disease when their symptoms are more debilitating 30 .…”
Section: Barriers To Clinical Trials For Admentioning
confidence: 99%
“…7,9,26 Moreover, inadequate targeted recruitment of diverse groups has exacerbated the underrepresentation of high-risk populations and limited our understanding of whether biomarker and pathological changes are similar across groups. 9,23,25,[27][28][29] These groups are also less likely to receive a timely AD diagnosis, and therefore when they are diagnosed, the diagnosis typically comes in the later stages of the disease when their symptoms are more debilitating. 30 This barrier is particularly important to overcome if we are to advance AD clinical research that is equitable and represents the full range of the AD patient population.…”
Section: Barriers To Clinical Trials For Admentioning
confidence: 99%
“…A lack of disease modifying treatments and growing evidence for dementia prevention [ 1 ] have meant there is increasing interest in recruiting those with higher genetic risk of dementia for investigation of disease mechanisms and targets for prevention and treatment. People from minority ethnic groups tend to be under-represented in dementia trials [ 50 ]. Not only does this mean we have limited understanding of whether treatments are effective in everyone, but it also misses the opportunity to study diverse mechanisms of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Deeper speculation into the differences in perception of preventive treatments between racial and ethnic groups is beyond the scope of this study; however, further research is needed to support racial equity in the HD community and the US healthcare system. By highlighting the importance of this demographic information in HD clinical studies, we can reduce the potential of race-based disparity in clinical trial enrollment observed in other neurodegenerative diseases [48,49].…”
Section: Discussionmentioning
confidence: 99%